Commentary: Modernism, Jews, and Frazer. Issue 3 (November 2015) - Silverman, Eric K.
Abstract: The outstanding papers in this collection raise important points for not only a fuller understanding of the contemporary Pacific, but also for issues of identity and belonging much further afield. Specifically, I propose that we can approach these papers from a Jewish Studies perspective gazing upon Melanesia, but also from a Melanesianist perspective surveying the broad field of Jewish Studies. For in many respects, the case studies ask us to rethink conventional boundaries. Melanesians, I argue, draw variously on Israelite, Israeli, Biblical, and Jewish themes, all refracted through Christianity, to re‐centre themselves in a global history so they are both valid and validated. But in so doing, we must ask ourselves, If Melanesians lay claim to Jewish affinities, broadly construed, what do these claims pose for Jewish identities as well as the very concept of identity in terms of notions of diaspora and centre? Indeed, if Melanesians are Jews, then how do we define not only Judaism but also Melanesia? My goal, then, is not so much to focus on the chapters as to use the chapters to probe fundamental questions about self and society in a globalised, mutable world.